Comparison of seroconversion rates between low-dose intradermal and recommended dose intramuscular hepatitis B vaccination in children - Sony HA Harsono; Zarkasih Anwar; Nancy Pardede (Paediatrica Indonesiana, 2003)
Introduction Massive hepatitis B vaccination is expensive. Re-sults of studies showed that reduced dosage given intradermallyto adults and intramuscularly to children were able to induceseroconversion.Objective To compare the anti-HBs seroconversion (seropositiveand seroprotective) rates between intradermal low-dose of 2 mg(ID-2) and intramuscular recommended dose of 10 mg (IM-10)vaccination against hepatitis B.Methods In a randomized clinical trial, using the hepatitis B plasmavaccine, elementary school children in Tanjung Enim subdistrict,80-168 months of age, were randomly assigned to be given threedoses of either the ID-2 (n=59) or IM-10 (n=64) vaccinations atone month intervals. Seropositive (anti HBs titer >2.1 mIU/l) andseroprotective (anti HBs >10 mIU/l) rates as well as the seroposi-tive and seroprotective geometric mean antibody titers (GMTs) werecompared one month after each inoculation. A p value of <0.1was considered statistically significant.Results One month after the third inoculation, there was no sig-nificant difference in the seropositive rate (95% vs. 89%),seroprotective rate (85% vs. 83%), seropositive GMTs (55.85 mIU/l vs. 61.24mIU/l), and seroprotective GMTs (73.86 mIU/l vs. 72.49mIU/l) between the ID-2 and the IM-10 groups (all with p>0.1)Conclusion Reduced doses of the hepatitis B vaccine given in-tradermally may offer protection against hepatitis B, thus it may beuseful for mass vaccination programs